Communication acoustics : an introduction to speech, audio, and psychoacoustics - Pulkki, Ville; Karjalainen, Matti, 1946-2010. (Chichester, West Sussex, United Kingdom : Wiley, 2015)
'This book aims to convey to engineering students and researchers alike the relevant knowledge about the nature of acoustics, sound and hearing that will enable them to develop new technologies in this area through acquiring a thorough understanding of how sound and hearing works. There is currently no technical book available covering the communication path from sound sources through medium to the formation of auditory events in the brain - this book will fill this gap in the current book literature. It discusses the multidisciplinary area of acoustics, hearing, psychoacoustics, signal processing, speech and sound quality and is suitable for use as a main course textbook for senior undergraduate and graduate courses related to audio communication systems. It covers the basics of signal processing, traditional acoustics as well as the human hearing system and how to build audio techniques based on human hearing resolution. It discusses the technologies and applications for sound synthesis and reproduction, and for speech and audio quality evaluation'--
Includes index.
Keywords: Sound -- recording and reproducing; Hearing; Psychoacoustics; Sound